INOVASI TEKNOLOGI MESIN POWER THRESER UNTUK PETANI PADI DI KABUPATEN DHARMASRAYA - Syahri, Budi; Refdinal, Refdinal; Aziz, Abdul (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
The purpose of implementing this community service activity is to improve the economy of the rice farming community in Dharmasraya Regency, especially Kenagarian Koto Baru. From the results of a survey conducted by the service team, an indication of the basic problem of farmers is in the process of handling rice at post-harvest. In this process, farmers spend a lot of energy, time and money because they tend to be carried out manually. Through this service activity, the service team tries to unravel the problems of farmers by making technological innovations for the power thereser machine. The science and technology offered in this activity is the construction of a power thereser machine that is equipped with a long blow. The function of this blowing tunnel is to efficiently separate filled rice and empty rice. So that the rice yields obtained by farmers are clean with the best quality of grain. The method of applying science and technology in this activity is to provide introductory theory, demonstration, practice and its application directly. The introductory theory is applicable, namely the introduction of tools, how to use them, their functions and application in the field. The results of the implementation of this activity provide significant benefits to the work process of farmers in operating the rice thresher machine. The level of satisfaction and assessment of farmers on this rice thresher machine is very high because it is effective in construction and efficient in operation